Optimization Design and Calculation of Mooring System Parameters based on Genetic Algorithm - Xia Liang-yu; Zhi Li; Chen Ling; Cheng Yue (MATEC Web of Conferences, 2018)
Based on the static equilibrium model of mooring system parameters, the multi - objective optimization model is established and the genetic algorithm is introduced as the optimization algorithm, which improves the crossover operator. Taking the example of a single point mooring system, concerned optimization design and calculation has been done. Compared with the general genetic algorithm, the result of this algorithm is superior, significantly improving the stability of the mooring system.